2012
DOI: 10.1002/ece3.285
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of MHC class I genes in the European badger (Meles meles)

Abstract: The major histocompatibility complex (MHC) plays a central role in the adaptive immune system and provides a good model with which to understand the evolutionary processes underlying functional genes. Trans-species polymorphism and orthology are both commonly found in MHC genes; however, mammalian MHC class I genes tend to cluster by species. Concerted evolution has the potential to homogenize different loci, whereas birth-and-death evolution can lead to the loss of orthologs; both processes result in monophyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
38
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(44 citation statements)
references
References 116 publications
5
38
1
Order By: Relevance
“…; Sin et al. ). Alternatively, females may make cryptic choices according to heterozygosity (Løvlie et al.…”
Section: Discussionmentioning
confidence: 98%
“…; Sin et al. ). Alternatively, females may make cryptic choices according to heterozygosity (Løvlie et al.…”
Section: Discussionmentioning
confidence: 98%
“…We used published primers to amplify exon 3 and exon 2 regions (Sin et al . ,c) that encode the antigen‐binding domain in MHC class I and class II DRB genes, respectively. Previous studies of the badger MHC indicated the presence of at least two class I loci and two class II DRB loci, with seven and four putatively functional sequences identified by transcription analysis, respectively (Sin et al .…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies of the badger MHC indicated the presence of at least two class I loci and two class II DRB loci, with seven and four putatively functional sequences identified by transcription analysis, respectively (Sin et al . ,c). The MHC sequences were separated by reference strand‐mediated conformation analysis (RSCA) following Sin (), in which each ‘RSCA allele’ was confirmed to be an individual, putatively functional, sequence.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations